Automatic load change coordinated control of air separation units. (March 2019) - Zou, Tao; Liu, Jianbang; Yu, Haibin; Zhang, Xin; Ma, Xiaolong
Abstract: An automatic load change coordinated control system is developed for strongly coupled and nonlinear air separation units. Firstly, a loosely coupled model is established to solve the tight coupling problem and a robust control strategy integrated with loosely coupled model and priority setting of controlled variables is formed. Secondly, an incremental load balancing calculation method is proposed to handle the nonlinearity and the external target of backflow valve opening is adjusted in real time to solve the hysteresis characteristic. Finally, the comprehensive energy consumption decreases by 2% through deploying the designed automatic control system in an actual air separation unit.